2019
DOI: 10.1021/acs.organomet.9b00013
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of a 1,5-Oligosilanylene Dianion Containing a Disiloxane Unit

Abstract: Synthesis of a number of disiloxane containing cyclo- and bicyclooligosilanes is described starting from the dipotassium 1,5-oligosiloxanylene diide derived from 1,3-bis[tris(trimethylsilyl)silyl]tetramethyldisiloxane. In addition, the use of this particular fragment as ligand for zinc and group 4 metallocene complexes was studied. Both types of compounds exhibit marked structural differences compared to related compounds containing Si-Si-Si units instead of the Si-O-Si fragment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 69 publications
(168 reference statements)
1
28
0
Order By: Relevance
“…The chemical shift of the resonance clearly indicates a very high degree of polarity of the Si–Y interaction, which is only slightly less polar than the respective magnesium compound [(DME)·Mg{Si(SiMe 3 ) 2 SiMe 2 } 2 O] (δ 29 Si = −166.7 ppm). 16 Such strong silanide character was neither observed for Tilley’s Cp* 2 YSiH(SiMe 3 ) 2 (δ 29 Si = −120.0 ppm, 1 J Si–Y = 92 Hz) 9 nor for Piers’ R(Me 3 Si) 2 SiYI 2 ·(THF) 3 (R = SiMe 3 : δ 29 Si = −134.7 ppm, 1 J Si–Y = 63 Hz; R = Et: δ 29 Si = −73.5 ppm, 1 J Si–Y = 71 Hz), 21 both of which are neutral complexes. The expected higher degree of covalent Si–Y interaction for the neutral compounds is nicely reflected by their larger 1 J Si–Y coupling constants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical shift of the resonance clearly indicates a very high degree of polarity of the Si–Y interaction, which is only slightly less polar than the respective magnesium compound [(DME)·Mg{Si(SiMe 3 ) 2 SiMe 2 } 2 O] (δ 29 Si = −166.7 ppm). 16 Such strong silanide character was neither observed for Tilley’s Cp* 2 YSiH(SiMe 3 ) 2 (δ 29 Si = −120.0 ppm, 1 J Si–Y = 92 Hz) 9 nor for Piers’ R(Me 3 Si) 2 SiYI 2 ·(THF) 3 (R = SiMe 3 : δ 29 Si = −134.7 ppm, 1 J Si–Y = 63 Hz; R = Et: δ 29 Si = −73.5 ppm, 1 J Si–Y = 71 Hz), 21 both of which are neutral complexes. The expected higher degree of covalent Si–Y interaction for the neutral compounds is nicely reflected by their larger 1 J Si–Y coupling constants.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, we treated 2Y with Cp 2 ZrCl 2 and obtained 1-zircona-4-oxatetrasilacyclohexane 3 ( Scheme 2 ), which had been prepared previously in the reaction of 1 with Cp 2 ZrCl 2 . 16 Another reaction of 2Y with InCl 3 gave the respective cyclic indium compound, 4 ( Scheme 2 ). Previously, it had been shown that the reactions of oligosilanylene diides with InCl 3 and GaCl 3 lead to formation of cyclic dichloroindate or -gallate complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the aforementioned silanolates. Complexes obtained in this way involve the cations Li + , [82–86] Na + , [87–89] K + , [85,87,89–91] Rb + , [89] Cs + , [87,89,92] Mg 2+ , [93] Sr 2+ , [94] Ba 2+ , [95,96] Sn 4+ , [97,98] Cr 2+/3+ , [99,100] Fe 3+ , [101] Y 3+ , [100,102] Zr 4+ , [103] Sm 2+ , [104] Tm 3+ , [105] Yb 2+ , [104,106–108] Th 4+ , [109–112] U 4+ , [109–113] and UO 2 2+ [114] . Hence, many siloxane⋅⋅⋅M n+ contacts might have been established over the years but are rather occasionally than purposefully realized.…”
Section: Siloxane Coordination Compoundsmentioning
confidence: 99%
“…The resulting building block is represented by the easily available disiloxane 1. Its treatment with two equivalents of t BuOK leads to the respective oligosilanylene diide 2 (Scheme 1) [11], which can be used as a versatile starting material for the preparation of larger molecular architectures containing oligosiloxane substructures [15].…”
Section: Introductionmentioning
confidence: 99%